2015
DOI: 10.1021/am506921y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Metal–MoS2Interface on MoS2Transistor Performance: Comparison of Ag and Ti Contacts

Abstract: In this work, we compare the electrical characteristics of MoS2 field-effect transistors (FETs) with Ag source/drain contacts with those with Ti and demonstrate that the metal-MoS2 interface is crucial to the device performance. MoS2 FETs with Ag contacts show more than 60 times higher ON-state current than those with Ti contacts. In order to better understand the mechanism of the better performance with Ag contacts, 5 nm Au/5 nm Ag (contact layer) or 5 nm Au/5 nm Ti film was deposited onto MoS2 monolayers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 48 publications
3
86
1
Order By: Relevance
“…In Ref. 64 it is found that MoS 2 /Ag gives a better contact than MoS 2 /Ti, due to a much smoother interface in the former case, suggesting to prefer physisorption over chemisorption.…”
Section: B Interface Potential Step and Schottky Barriermentioning
confidence: 99%
“…In Ref. 64 it is found that MoS 2 /Ag gives a better contact than MoS 2 /Ti, due to a much smoother interface in the former case, suggesting to prefer physisorption over chemisorption.…”
Section: B Interface Potential Step and Schottky Barriermentioning
confidence: 99%
“…and group III–VI nanomaterials (InSe,38, 39, 40, 41, 42 GaSe,43, 44, 45, 46, 47, 48 etc.) have been extensively investigated in many fields including photodetectors,49, 50, 51, 52, 53, 54, 55, 56, 57, 58 gas sensors,59, 60 field effect transistors (FETs),38, 61, 62, 63, 64, 65 and flexible devices 66, 67, 68…”
Section: Introductionmentioning
confidence: 99%
“…The first one is the phenomenon of Fermi‐level pinning , meaning that the carrier injection is always constrained, though, to different extent, by the Schottky barrier formed at metal–semiconductor (M–S) interface. Low work function metal such as Sc , Al , and Ag have been proved producing superior transistor performance than conventional high work function metal (like Ni and Au); the second limitation originates from the inherent surface defects found on natural MoS 2 crystal. High density of sulfur rich/deficient sites on a freshly exfoliated MoS 2 crystal render localized p‐ or n‐type conduction and variation of the electronic properties from sample to sample .…”
Section: Introductionmentioning
confidence: 99%